The Phenomenon of Ambivalence in Policy Implementation: How Muhammadiyah Universities Protect Women against Sexual Violence - Ria Angin; Fauziah Fauziah; Kahar Haerah (Universitas Muhammadiyah Tangerang, 2024)
This article discusses